2008
DOI: 10.1080/03079450801929941
|View full text |Cite
|
Sign up to set email alerts
|

The vaccination-challenge trial: the gold standard test to evaluate the protective efficacy of infectious coryza vaccines

Abstract: Infectious coryza is an upper respiratory tract disease of chickens with the major impact occurring in multiage flocks. We investigated the relationship between the level of antibodies, as detected by a haemagglutination-inhibition (HI) assay, in infectious coryza-vaccinated chickens and the protection against challenge in those chickens. In one experiment, chickens given a single dose of either of two infectious coryza vaccines lacked a detectable HI response to vaccination but showed significant levels of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…paragallinarum in poultry indicated a significant induction of immune responses to the HA antigen (Iritani et al 1980;Kume et al 1980;Sawata et al 1980) that were correlated with protection in birds and correspondingly the host response against a particular antigenic epitope of Av. parallinarum has been largely utilized for the estimation of vaccine-mediated efficacy (Takagi et al 1991;Hsu et al 2007;Garcia et al 2008). In the present study, a similar immune-protection due to the presence of circulatory HI antibodies was noted in Japanese quail as evident by lack of clinical sign development.…”
Section: Discussionsupporting
confidence: 74%
“…paragallinarum in poultry indicated a significant induction of immune responses to the HA antigen (Iritani et al 1980;Kume et al 1980;Sawata et al 1980) that were correlated with protection in birds and correspondingly the host response against a particular antigenic epitope of Av. parallinarum has been largely utilized for the estimation of vaccine-mediated efficacy (Takagi et al 1991;Hsu et al 2007;Garcia et al 2008). In the present study, a similar immune-protection due to the presence of circulatory HI antibodies was noted in Japanese quail as evident by lack of clinical sign development.…”
Section: Discussionsupporting
confidence: 74%
“…15,16 It is further important to note that during course of such vaccine development and in other subsequent studies particularly, it was observed that single shot immunization of tetravalent vaccine does not yield appreciable immune response, but evoked good protection in host in terms of survivality/life expectancy and clinical sign development, while double shot immunization at 8 weeks apart yielded both relevant immune response and protection against the diseases, therefore questioned definitive predictor for vaccine efficacy in future. 49 Having such inconclusive insight on protective efficacy of several developed vaccines, some researcher considered certain factors as a hindrance to evaluate the vaccine efficacy and they are as infection dosage, individual differences of the host's (chicken) and choice of infection model, besides non-standardisation of pathogenicity effects on host which is otherwise markedly complicated. 50 Their studies also suggested that natural way of disease transmission phenomenon or simulated manner of disease transmission during experimentation could reflect valuable information on natural process of spreading, sticking and proliferation of germs among hosts (birds) and may evaluate the definite understanding to pathopoietic mechanism of Avibacterium paragallinarum to suggest variance seen in vaccine efficacy study.…”
Section: Newer Knowledge On Therapeutic and Prophylactic Measures Agamentioning
confidence: 99%
“…Garcia et al . [20] demonstrated that over 90% of vaccinated chickens have titers more than 5 HI if the chickens receive more than one vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted by Garcia et al . [20] mentions that the challenge test is the gold standard to determine the immunological response in chickens that have been vaccinated with a double dose of A. paragallinarum . Based on the challenge test, both the severity of symptoms and pathological changes will be known.…”
Section: Resultsmentioning
confidence: 99%